Marginalization Problems of Former State Agricultural Farms Area in the West Pomeranian Voivodship - Jasiulewicz, Michał (Regional Barometer. Analyses & Prognoses, 2011)
The paper is devoted to the marginalization problems of former state Agricultural Farms area of West Pomeranian Voivodeship. The paper is devoted to the analysis of marginalization in the areas of Stale Agricultural Farms domination in the frost. As a indicators of the degree of marginalization three characteristics have been taken into the consideration: a) unemployment in the years 2006–2008, b) average salary in the districts of the analized area, c) new constructions of residential buildings.